Saper vedere: il “giro lungo” dell’antropologia visuale - Chiozzi, Paolo (SocietàMutamentoPolitica, 2016)
Visual anthropology is often identified with ‘Ethnographic film’, thus the debate focuses more on filming than on ethics of anthropological research. In this paper I suggest a different approach to visual research, where the anthropologist does not abdicate his cultural and ‘political’ tasks to become a filmmaker, but is aware that he must ‘learn’ (and teach) how to see human reality. And my long wandering through visual anthropology allowed me to realize that one can be a good ‘visual’ anthropologist even if he does not make himself films or professional photographs – on the contrary I believe that the collaboration between the anthropologist and the photographer is often much more suitable. What we should do, is to interact and collaborate with professional filmmakers and/or photographers who share our own ideas about the ‘observation’ of humans: not a sort of voyeurism, but an emotional sharing of their memories, of their daily life, of their emotions, of their fears – and of course the awareness that anthropology has an intrinsic ‘political’ involvement. Here my aim is to explain my own approach through some examples of anthropological research based on a tight collaboration with photographers (Davide Virdis, acrhitect and photographer – Stefano Morelli, psychologist and photographer – Mario Chieffo, freelance photographer), and one specific work done involving also a filmmaker, Sandro Nardoni. Those works are actually steps of a route that led me to realize how dangerous the overemphasis of our sense of seeing may be.